Method for producing topical hemostatic material, and topical hemostatic material
A cationized cellulose-based hemostatic material is produced by applying a viscous cellulose solution to a base material, addressing the need for effective, low-impact hemostasis with reduced tissue damage and allergenic risks, achieving enhanced adhesion and hemostatic efficacy.
Patent Information
- Application Number
- JP2021567724
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-12-26
- Filing Date
- 2020-12-25
- Publication Date
- 2025-01-08
- Estimated Expiration
- 2040-12-25
AI Technical Summary
There is a need for local hemostatic materials that have minimal impact on the human body, are cost-effective, and exhibit strong hemostatic effects, while avoiding the drawbacks of existing methods such as tissue damage and allergenic risks.
A method involving the application of a cationized cellulose aqueous solution with a predetermined viscosity to a base material, followed by drying, to create a local hemostatic material with a layer of cationized cellulose on one side, achieving a viscosity of 13 mPa·s or more.
The resulting hemostatic material effectively promotes blood coagulation at bleeding sites with reduced tissue damage and allergenic risks, demonstrating superior adhesion times and hemostatic performance compared to existing materials.
Smart Images

Figure 0007610196000011 
Figure 0007610196000012 
Figure 0007610196000013
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a topical hemostat.The present invention also relates to a topical hemostat. [Background technology]
[0002] Bleeding is a phenomenon in which blood vessels rupture for some reason, causing blood to leak from inside the vessel to outside the vessel. The classic method for stopping bleeding is to directly apply pressure to either the blood vessel or the body on the outside of the blood vessel. Hemostasis by pressure is inconvenient because it must be maintained until the bleeding is controlled. During surgery, a method of stopping bleeding is used in which heat is applied to the surrounding tissue, including the bleeding blood vessel, to cauterize it, but this can cause damage to the surrounding tissue. Other methods of stopping bleeding include the use of compounds such as collagen or oxidized cellulose.
[0003] Chitosan is also used as a local hemostatic agent. Chitosan has a high hemostatic effect (Patent Document 1), but caution is required when used by people who have allergies to shellfish.
[0004] Cationic cellulose is a water-soluble polymer that is widely used in daily necessities such as shampoos because it has little effect on the human body and is inexpensive. It has been found that cationic cellulose exhibits antibacterial properties and hemostatic properties, and is expected to be used as a hemostatic agent (Patent Document 2). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2016-522208 A [Patent Document 2] JP 2017-140231 A Summary of the Invention [Problem to be solved by the invention]
[0006] In the field of hemostasis, there is a demand for topical hemostatic materials that are less harmful to the human body, are inexpensive, and exhibit good hemostatic properties. [Means for solving the problem]
[0007] The present invention was made based on the discovery that a local hemostatic material prepared by applying an aqueous solution of cationic cellulose having a predetermined viscosity to at least one surface of a substrate and then drying the aqueous solution exhibits excellent hemostatic effect. Specifically, the present invention provides the following local hemostatic material, a method for producing the local hemostatic material, and a mixed solution for producing the local hemostatic material.
[0008] One aspect of the present invention provides a method for producing a topical hemostat, comprising the steps of applying a mixed liquid containing cationized cellulose in a solvent to at least one surface of a substrate; and removing the solvent, wherein the mixed liquid has a viscosity of 13 mPa s or more.
[0009] Another aspect of the present invention provides a topical hemostat comprising a substrate having applied to at least one side thereof a mixture comprising cationized cellulose in a solvent, the mixture having a viscosity of 13 mPa s or greater.
[0010] Another aspect of the present invention provides a topical hemostatic material comprising a substrate having a first main surface and a layer containing cationic cellulose on the side of the first main surface, the layer containing cationic cellulose having a thickness of 6.7 μm or more.
[0011] Another aspect of the present invention provides a mixture comprising cationized cellulose in a solvent, the mixture having a viscosity of 13 mPa s or more, for producing a topical hemostat comprising a substrate and a layer comprising cationized cellulose on at least one side of the substrate. [Brief description of the drawings]
[0012] [Figure 1] Fig. 1(a) is an exploded side view of a topical hemostat according to one embodiment of the present invention, and Fig. 1(b) is a front view of the topical hemostat. [Diagram 2] FIG. 2 is a scatter plot showing the adhesion time of various hemostatic pads to a glass plate via blood. [Diagram 3] FIG. 3 is a scatter plot showing the relationship between the viscosity of an aqueous solution of cationized cellulose and the adhesion time of a hemostatic pad made using the aqueous solution to a glass plate via blood. [Figure 4] FIG. 4 is a graph showing the relationship between the thickness of the layer containing cationic cellulose and the adhesion time of the hemostatic film to a glass plate via blood. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] In the present specification, the term "local hemostatic material" refers to a composition that can promote blood clotting outside the blood vessel at the bleeding site, and that includes cationic cellulose and a substrate. The local hemostatic material can be produced by applying a mixture containing cationic cellulose in a solvent to at least one surface of a substrate; and removing the solvent. The local hemostatic material produced by the above-mentioned production method includes, but is not limited to, a substrate and a layer containing cationic cellulose on at least one surface side of the substrate. In the present specification, the local hemostatic material that can be obtained by applying the mixture to at least one surface of an absorbent pad and performing a process of removing the solvent from the mixture is also referred to as a "hemostatic pad".
[0014] In one embodiment, a topical hemostatic material including a layer containing cationized cellulose includes a substrate having a first main surface, and a layer containing cationized cellulose on the side of the first main surface, the layer containing cationized cellulose having a thickness of 6.7 μm or more. In one embodiment, a topical hemostatic material including a layer containing cationized cellulose includes a substrate having a first main surface and a second main surface opposite to the first main surface, a layer containing cationized cellulose on the side of the first main surface of the substrate, and a backing member having a first main surface fixed to the second main surface of the substrate, the layer containing cationized cellulose having a thickness of 6.7 μm or more.
[0015] In the present specification, the "substrate" may be any structure capable of holding cationized cellulose on its surface. The substrate has, for example, a first main surface and a second main surface opposite to the first main surface. The shape of the substrate is not particularly limited, but is a shape suitable for use at the application site. The substrate has, for example, a surface capable of covering the bleeding site. The substrate may be in the form of, for example, an absorbent pad or a film. The substrate has a surface of various shapes, for example, a polygonal shape such as a rectangle, a square, an oval, or a pentagon, a circle, an oval, or an ellipse, and can hold cationized cellulose on its surface. The substrate may be made of at least one material selected from the group consisting of, but not limited to, thread, woven thread, lace, felt, nonwoven fabric, natural fiber (e.g., cotton), synthetic fiber (e.g., rayon), synthetic resin (polyethylene terephthalate (PET)), and synthetic film. The substrate may be commercially available, for example, tablet cotton balls (F3 Co., Ltd.); gauze; bandages; polyester films such as PET and polybutylene terephthalate; polyolefin films such as polyethylene and polypropylene; polyvinyl chloride films; polycarbonate films; polyurethane films such as polyether urethane and polyester urethane; or laminates of two or more of these.
[0016] In this specification, the term "absorbent pad" refers to a structure capable of holding cationized cellulose on its surface and absorbing liquid. The absorbent pad may be, for example, a polygonal prism, a rectangular parallelepiped, or a cylinder having a rectangular or elliptical surface with a short side of 1 to 3 cm and a long side of 2 to 5 cm, and a thickness of 2 to 10 mm. The absorbent pad may be, for example, a cylinder having a circular surface with a diameter of 1 to 3 cm, and a thickness of 2 to 10 mm. The absorbent pad may be manufactured, for example, by compressing natural fibers such as cotton and silk, or synthetic fibers such as polypropylene and / or polyethylene.
[0017] As used herein, a "backing member" has a second surface facing the skin and a first surface facing away from the skin opposite the second surface, although this is not necessary for the practice of the invention. The backing member may have a variety of shapes, such as, for example, rectangular, square, oval, circular, oval, elliptical, and heart-shaped. The backing member may be, but is not limited to, thin, highly flexible or deformable, and water impermeable. The backing member may be transparent or opaque. The thickness of the backing member may be, but is not limited to, 0.05 to 0.2 millimeters.
[0018] The backing member may be, but is not limited to, a polyester film, a polyethylene film, a polyurethane stretchable elastomeric film, or any other flexible water-insoluble polymeric film known in the art, In other examples, the backing member may be made of polyolefin, vinyl polyethylene acetate, nonwoven fabric, rubber, or other materials known in the art.
[0019] The first surface of the backing member comprises an adhesive layer that adheres the hemostatic pad and allows for adhesion of the topical hemostatic material to the skin. The adhesive layer includes, but is not limited to, an adhesive that is biocompatible with human skin. The adhesive may be water-soluble, water-insoluble, or dispersible in an aqueous environment, and any adhesive available in the art may be used without limitation. The adhesive may be, for example, an acrylic adhesive. The adhesive layer may be configured in a continuous pattern or may be configured in a discontinuous pattern, such as lines or a screen.
[0020] As used herein, a "release paper" is a paper having a first surface facing the first surface of the backing member and a second surface opposite the first surface and including a direction away from the first surface of the backing member. The release paper covers the entire first surface of the backing member until immediately before the topical hemostatic material is used, thereby protecting the first surface of the backing member from contamination during storage or transportation. The release paper may be coated with a silicone resin or the like on the first surface facing the hemostatic pad and the first surface of the backing member.
[0021] As used herein, "cationized cellulose" refers to a cellulose-based polymer having cationic groups. Cationic cellulose can be represented, for example, by the following general formula: [ka] [In the formula, At least one R1 is -R2-N+(R3)(R4)(R5)·X-; The other R1 of said R1 is -H or -(CH2CH2O)mH, R2 is C1-6 alkylene, C2-6 hydroxyalkylene, -(CH2CH2O)l-, or a combination thereof; l is 1 or 2; m is 1 or 2; X- is an anionic group, R3, R4, and R5 are C1-6 alkyl, C1-6 alkenyl, O-C1-6 alkyl, heteroalkyl or heteroalkenyl of CaYb, Y is a heteroatom, a+b is 4 to 6, and when bonded at a nitrogen atom, form a saturated or unsaturated 5- or 6-membered ring containing the nitrogen atom.
[0022] In one example, the at least one R1 is -CH2CHO-CH2CH(OH)CH2-N+(R3)(R4)(R5)·X-, where R3, R4, and R5 may be methyl or ethyl groups. In another example, the at least one R1 is -CH2CH(OH)CH2N+(R3)(R4)(R5)·X-, where R3, R4, and R5 may be methyl or ethyl groups. In another example, the anionic group may be a halide ion, a phosphate ester group, a carboxyl group, a sulfonic acid group, or a sulfate ester group. The halide ion may be a fluoride ion, a chloride ion, a bromide ion, or an iodide ion.
[0023] Cationic cellulose can be produced based on known methods. In one example, cationic cellulose can be obtained by partially chemically bonding hydroxyethyl cellulose with glycidyl trimethyl ammonium chloride or 3-chloro-2-hydroxypropyl trimethyl ammonium chloride. In another method, cationic cellulose can be obtained by the method described in Patent Document 2. Cationic cellulose is also commercially available, and may be, for example, Poise C-60H (Kao Corporation) or Poise C-150H (Kao Corporation).
[0024] It is known that cationic cellulose dissolved in a solution attracts red blood cells and platelets due to its positive charge and promotes blood clotting (Patent Document 2). In one example, at least one of the other R1 may be -(CH2CHO)mH. The cationic cellulose in this example has higher water retention and is therefore suitable for moist wound healing. In another example, any of the hydroxyl groups at the 2-, 4-, and 6-positions of glucose forming cellulose is modified with a cationic functional group.
[0025] The "layer containing cationized cellulose" is a structure containing cationized cellulose. The layer containing cationized cellulose can be formed, for example, by applying a mixed solution containing cationized cellulose in a solvent to the surface of a structure, and then removing the solvent from the mixed solution. The thickness of the cationized cellulose can be measured as a physical distance using a general measuring instrument such as a micrometer, a microscope, or a vernier caliper. Specifically, the thickness of the cationized cellulose can be measured using a micrometer or a microscope. The thickness of the layer containing cationized cellulose may be constant or may not be constant. When the thickness of the layer containing cationized cellulose is not constant, the thickness of the layer containing cationized cellulose may be measured at seven different points on one product, and the thickness of the layer containing cationized cellulose may be the average value of the thicknesses at five points excluding the data at two points showing the maximum and minimum values. The seven points at which the thickness is measured may be at a distance of half the radius of the inscribed circle from the center point of the inscribed circle of the layer containing cationized cellulose as viewed from a direction perpendicular to the main surface of the layer containing cationized cellulose, and may be equally spaced around the center point.
[0026] The thickness of the layer containing cationic cellulose is, for example, 6.7 μm or more, 7 μm or more, 8 μm or more, 9 μm or more, 10 μm or more, 15 μm or more, 16 μm or more, 17 μm or more, 18 μm or more, 19 μm or more, 20 μm or more, 25 μm or more, 30 μm or more, 50 μm or more, or 75 μm or more. The thickness of the layer containing cationic cellulose is, for example, 150 μm or less, 125 μm or less, 100 μm or less, 90 μm or less, or 80 μm or less. The thickness of the layer containing cationic cellulose may be within a range that appropriately combines the numerical values related to the layers disclosed in this specification, and may be, for example, 6.7 μm to 150 μm, 7 μm to 150 μm, 8 μm to 150 μm, 9 μm to 150 μm, 10 μm to 150 μm, 15 μm to 150 μm, 16 μm to 150 μm, 17 μm to 150 μm, 18 μm to 150 μm, 19 μm to 150 μm, 20 μm to 150 μm, 25 μm to 150 μm, 30 μm to 150 μm, 50 μm to 150 μm, or 75 μm to 150 μm.
[0027] In the present specification, the term "mixture containing cationized cellulose in a solvent" refers to a liquid containing cationized cellulose and a solvent. The mixture can be prepared, for example, by adding cationized cellulose to a solvent. The mixture can be obtained, but is not limited to, by adding powdered cationized cellulose to water and continuing to stir until the water becomes transparent. In another example, the mixture can be obtained by diluting cationized cellulose contained in a high concentration in a solvent with a solvent.
[0028] One embodiment is a topical hemostat comprising a substrate and a layer comprising cationic cellulose on at least one side of the substrate, and a mixture comprising cationic cellulose in a solvent for producing the topical hemostat, the mixture having a viscosity of 13 mPa s or more.
[0029] The mixture containing cationic cellulose in a solvent may contain other components, but is not limited to these. The other components may be, for example, antibiotics, analgesics, anti-inflammatory drugs, hemostatic agents, skin softeners, hemostatic agents, steroids, softeners, fragrances, colorants, cooling agents, agents with a warming effect, cellulose and collagen for making the layer containing cationic cellulose stronger, or a combination thereof. The hemostatic agent may be, for example, collagen, oxidized cellulose, gelatin, and thrombin, or a combination thereof. The layer containing other components and cationic cellulose may be formed, for example, by applying a mixture containing cationic cellulose and other components in a solvent medium to the surface of a structure, and then removing the solvent from the mixture.
[0030] The "solvent" may be, but is not limited to, water or an alcohol. The alcohol may be, for example, any one of methanol, ethanol, and propanol, or a mixture thereof.
[0031] The viscosity of the mixture containing the cationized cellulose in the solvent is measured by a B-type rotational viscometer. The mixture containing the cationized cellulose in the solvent preferably has a viscosity of 13 mPa·s or more. The mixture has a viscosity of 16 mPa·s or more, 25 mPa·s or more, 50 mPa·s or more, or 100 mPa·s or more. From the viewpoint of a more preferable hemostatic effect, the mixture has a viscosity of 0.1 Pa·s or more, 0.2 Pa·s or more, 0.3 Pa·s or more, 0.4 Pa·s or more, 1.8 Pa·s or more, 2 Pa·s or more, 2.2 Pa·s or more, 4 Pa·s or more, 4.2 Pa·s or more, 4.5 Pa·s or more, 8 Pa·s or more, 9 Pa·s or more, 10 Pa·s or more, 11 Pa·s or more, 50 Pa·s or more, 60 Pa·s or more, 70 Pa·s or more, 80 Pa·s or more, 90 Pa·s or more, 100 Pa·s or more, or 110 Pa·s or more.
[0032] The viscosity of the mixed liquid containing the cationized cellulose is, for example, 150 Pa·s or less, 140 Pa·s or less, 130 Pa·s or less, 120 Pa·s or less, or 115 Pa·s or less. The viscosity of the mixed liquid containing cationized cellulose may be in a range that is an appropriate combination of the numerical values related to viscosity disclosed in the present specification, and may be, for example, 13 mPa·s to 150 Pa·s, 16 mPa·s to 150 Pa·s, 25 mPa·s to 150 Pa·s, 50 mPa·s to 150 Pa·s, 0.1 to 150 Pa·s, 1 to 150 Pa·s, 1.8 to 150 Pa·s, 2 to 150 Pa·s, 4 to 150 Pa·s, 8 to 150 Pa·s, 10 to 150 Pa·s, 50 to 150 Pa·s, 60 to 150 Pa·s, 70 to 150 Pa·s, 80 to 150 Pa·s, 90 to 150 Pa·s, 100 to 150 Pa·s, or 110 to 150 Pa·s.
[0033] The molecular weight of the cationic cellulose is measured by the copper ethylenediamine method (JIS 8215). The viscosity of a mixture containing a cationic cellulose having a large molecular weight tends to be higher than that of a mixture containing a cationic cellulose having a smaller molecular weight at the same concentration (w / w%). In the case of a cationic cellulose having a large molecular weight, a mixture having a predetermined viscosity can be obtained with a smaller amount of cationic cellulose than that of a cationic cellulose having a smaller molecular weight. The molecular weight of the cationic cellulose is, for example, 600,000 or more, 800,000 or more, preferably 1,000,000 or more, 1,200,000 or more, 1,400,000 or more, and more preferably 1,500,000 or more.
[0034] The molecular weight of the cationized cellulose is, for example, 3,000,000 or less, 2,500,000 or less, or 2,000,000 or less. The molecular weight of the cationized cellulose may be within a range that appropriately combines the numerical values related to molecular weight disclosed in the present specification, for example, 600,000 to 3,000,000, 800,000 to 3,000,000, 1,000,000 to 3,000,000, 1,200,000 to 3,000,000, 1,400,000 to 3,000,000, or 1,500,000 to 3,000,000.
[0035] The mixture containing cationized cellulose can be applied to a substrate by spreading the mixture on at least one surface of the substrate using an instrument such as, but not limited to, a dispenser, a spatula, etc. The mixture containing cationized cellulose in a solvent is applied to, for example, 50% or more, 60% or more, 70% or more, 80% or more, 90% or more, 95% or more, 97% or more, 99% or more, or 100% of the total area of at least one surface of the substrate.
[0036] The solvent of the mixture applied to the substrate is removed using a known method for removing solvents such as water or alcohol, for example, by placing the substrate in a closed container with a desiccant such as silica gel, by heating, or by placing the substrate under reduced pressure, or a combination thereof.
[0037] The solvent of the mixed solution applied to the substrate by the removal process may not be completely removed, but is not limited to this. In one example, the solvent of the mixed solution applied to the substrate may be removed by 60% or more, 70% or more, 80% or more, 90% or more, 95% or more, or 100%. The solvent removal rate is calculated, for example, by calculating the weight of the solvent removed from the weight of the substrate before and after the removal process, and dividing the weight of the solvent removed by the weight of the solvent of the mixed solution applied to the substrate.
[0038] In one embodiment, the topical hemostat includes, but is not limited to, a substrate and a layer comprising cationic cellulose disposed on at least one surface of the substrate.
[0039] In the examples of the present specification described later, the excellent hemostatic effect of the topical hemostatic material according to the embodiment of the present invention was demonstrated. It is believed that the excellent hemostatic effect can be exhibited in the layer containing cationic cellulose in the topical hemostatic material because the positively charged cationic cellulose attracts the negatively charged red blood cells and platelets in the blood.
[0040] In one example, a hemostatic pad includes a substrate and a layer comprising cationized cellulose disposed on at least one surface of the substrate. The layer comprising cationized cellulose can be prepared by applying a mixture comprising cationized cellulose in a solvent as described herein to at least one surface of the substrate, including, but not limited to, the mixture, and removing the solvent. One embodiment of the present invention provides a mixture comprising cationized cellulose in a solvent for the manufacture of a topical hemostatic material comprising a substrate and a layer comprising cationized cellulose disposed on at least one surface of the substrate, the mixture having a viscosity of 13 mPa·s or more.
[0041] With reference to FIG. 1, a local hemostatic material 1 according to one embodiment of the present invention will be described. However, these embodiments are illustrative of the present invention and are not intended to limit in any way the invention described in the appended claims.
[0042] As shown in FIG. 1(a), the topical hemostatic material 1 includes a hemostatic pad 2. The hemostatic pad 2 is composed of cationic cellulose and an absorbent pad. The hemostatic pad 2 is an absorbent pad having a layer (not shown) containing cationic cellulose. The absorbent pad is a cylindrical cotton tablet. The hemostatic pad 2 has a first surface 21 facing the skin and a second surface 22 opposite to the first surface 21 and facing away from the skin. The hemostatic pad 2 has a layer containing cationic cellulose on the side of the first surface 21.
[0043] The topical hemostatic material 1 includes a backing member 3. The backing member 3 has a first surface 31 that faces the skin and a second surface 32 that faces away from the skin opposite the first surface 31. The first surface 31 of the backing member 3 is adhered to the second surface 22 of the hemostatic pad 2. The first surface 31 of the backing member 3 has an adhesive layer that includes a biocompatible acrylic adhesive.
[0044] The topical hemostatic material includes a first release paper 41 and a second release paper 42. As shown in FIG. 1(a), the first release paper 41 covers the left half of the first surface 21 of the hemostatic pad 2 and the left half of the first surface 31 of the backing member 3. As shown in FIG. 1(a), the second release paper 42 covers the right half of the first surface 31 of the hemostatic pad 2 and the right half of the first surface 31 of the backing member 3. In this embodiment, the release paper is a combination of two sheets, but is not limited thereto. The first surface of the hemostatic pad 2 and the first surface 31 of the backing member 3 may be entirely covered with one release paper, or may be entirely covered with three or more release papers.
[0045] As shown in FIG. 1( b ), the topical hemostatic material 1 includes a hemostatic pad 2 located approximately in the center of a backing member 3 .
[0046] Specific examples will be described below, which are intended to illustrate preferred embodiments of the present invention and are not intended to limit the invention described in the appended claims in any way. EXAMPLES
[0047] Example 1 [Preparation of cationic cellulose aqueous solution] The following Poise C-60H was added to purified water and stirred to prepare 1 w / w%, 2 w / w%, 4 w / w%, 0.2 w / w%, 0.3 w / w%, 0.4 w / w% and 0.5 w / w% cationic cellulose aqueous solutions (hereinafter also referred to as test solutions 1, 2, 3, 7, 8, 9 and 10, respectively). Similarly, 1 w / w%, 2 w / w% and 4 w / w% cationic cellulose aqueous solutions (hereinafter also referred to as test solutions 4, 5 and 6, respectively) were prepared from Poise C-150L. [Table 1] * O-[2-hydroxy-3-(trimethylammonio)propyl]hydroxyethylcellulose chloride
[0048] [Viscosity measurement] The viscosities of the prepared test liquids 1 to 10 were measured using a B-type rotational viscometer. The results are summarized below. [Table 2]
[0049] As shown in Table 2, Test Solution 1 had a viscosity of 41.9 mPa·s (measured value), while Test Solution 2 had a viscosity of 267 mPa·s (measured value). The molecular weight of the cationic cellulose contained in Test Solution 1 was equal to that of the cationic cellulose contained in Test Solution 2, both of which were 600,000, but the content concentration was 1 w / w% in Test Solution 1, whereas it was a higher concentration of 2 w / w% in Test Solution 2. This indicates that aqueous solutions containing higher concentrations of cationic cellulose have higher viscosities. In fact, Test Solution 3, which contained an even higher concentration of cationic cellulose (4 w / w%), had a molecular weight equal to 600,000, but showed a higher viscosity (4,192 mPa·s) (Table 2).
[0050] Test solution 2 had a viscosity of 267 mPa s (measured value), while test solution 5 had a viscosity of 10,100 mPa s (measured value). The concentration of cationic cellulose contained in test solution 2 and test solution 5 was equal at 2 [w / w%], but the molecular weight was 600,000 in test solution 2, while test solution 5 had a higher molecular weight of 1,500,000. This indicates that an aqueous solution containing cationic cellulose with a higher molecular weight has a higher viscosity.
[0051] [Preparation of local hemostatic material] 0.05g of test liquid 1 was applied to one side of compressed cotton, which is a disk-shaped (diameter 10mm x height 1.5mm) first aid bandage (product name: Niproen Pad S size) using a dispenser. The compressed cotton was transferred into a sealed container containing silica gel and dried overnight at room temperature to prepare hemostatic pad 1. In the same manner as test liquid 1, hemostatic pads 2 to 6 were prepared for test liquids 2 to 6, respectively.
[0052] [Hemostasis test] Whole blood samples A to E were collected from five volunteers. A few drops of each of the collected whole blood samples A to E were placed on a glass plate, and the following topical hemostatic materials were placed on top of the drops to contact the glass plate via the blood. [Table 3]
[0053] After contact between the topical hemostat and the glass plate, the topical hemostat was pressed against the glass plate for 30 seconds. The time until the topical hemostat stopped moving (adhesion time) was then recorded at 30-second intervals. In the hemostatic test, a shorter time (minutes) until the topical hemostat adhered to the glass plate indicates a higher hemostatic effect. The results for each topical hemostat are summarized below (Table 4 and Figure 2). A paired two-tailed t-test against Empad S was performed for each test result. [Table 4] *p<0.05 **p<0.01 ns not significant
[0054] As shown in Table 4, the Enpad S for covering protection required an average of 15.6 minutes to adhere to the glass plate in the hemostatic test, whereas the hemostatic pads 1 to 6 all adhered to the glass plate in a shorter time (average 7.4 minutes to average 1.0 minutes). This shows that the hemostatic pads using cationic cellulose have excellent hemostatic properties.
[0055] The Hemostatic Bandage Plus, which is also expected to have hemostasis due to alginate, showed an average adhesion time of 6.3 minutes, while Hemostatic Pads 1 to 6 showed almost the same or shorter adhesion times (average 7.4 minutes to average 1.0 minutes). This suggests that the hemostatic pad, which is expected to have hemostatic action due to cationic cellulose, shows hemostatic action equivalent to or better than that of topical hemostatic materials, which are expected to have hemostatic action due to alginate.
[0056] Hemostatic pads 2 to 6 showed a significantly shorter adhesion time than that of Empad S (t-test in Table 4). This indicates that the topical hemostatic material, which is expected to have a hemostatic effect due to cationic cellulose, has an excellent hemostatic effect.
[0057] Hemostatic pads 2 to 6 showed shorter adhesion times (average 5.2 to 1.0 minutes) than hemostatic pad 1 (average 7.4 minutes). As shown in Table 2, compared to the viscosity of hemostatic pad 1 (60 mPa·s (estimated value)), hemostatic pads 2 to 6 all showed higher viscosities (267 mPa·s to >100 mPa·s) (Table 5). These results indicate that there is a correlation between the viscosity of the aqueous solution used to prepare the local hemostatic material, which is expected to have a hemostatic effect due to cationic cellulose, and the local hemostatic material prepared by drying the aqueous solution.
[0058] [Relationship between viscosity and adhesion time] The relationship between the viscosity of each hemostatic pad shown in Table 2 and the adhesion time (average value) of each hemostatic pad shown in Table 4 is summarized below (Table 5 and FIG. 3). [Table 5]
[0059] As shown in Figure 3, the higher the viscosity of the topical hemostat, the shorter the adhesion time. This indicates that the viscosity of the aqueous solution used to prepare the topical hemostat affects the hemostatic effect of the topical hemostat, and that the higher the viscosity of the aqueous solution used to prepare the topical hemostat, the better the hemostatic effect of the topical hemostat. For example, hemostatic pad 6 made with test solution 6, which showed a higher viscosity, showed excellent hemostatic effect, similar to topical hemostats (Neoplaster CMC or Hemcondot) that are expected to have excellent hemostatic effect due to carboxymethylcellulose or chitosan (Table 4).
[0060] Example 2 [Thickness of layer containing cationic cellulose] 0.0637 mg of test liquid 10 was applied to one surface of a 10 mm square PET film using a dispenser. The PET film was transferred into a sealed container containing silica gel and dried overnight at room temperature to prepare a hemostatic film 1. Test films 2, 3, 5 and 6 were prepared using test liquids 1, 4, 2 and 6 in the same manner as above. An aqueous solution (1.5 w / w%) containing the cationized cellulose (Poise C-60H) with a molecular weight of 600,000 used in Example 1 was prepared. Hemostatic film 4 was prepared using the 1.5 w / w% aqueous solution of cationized cellulose prepared in the same manner as above. Six sheets of each hemostatic film were prepared.
[0061] The thickness of the layer containing cationic cellulose formed on one surface of each of the hemostatic films 1 to 6 was measured using a micrometer (manufactured by Mitutoyo Co., Ltd.). Specifically, the thickness of each film was measured at seven points, and the thickness was expressed as the average value of the five points excluding the two points showing the maximum and minimum values. The thickness [μm] of the layer containing cationic cellulose was calculated by subtracting the thickness [μm] of the PET film (control) to which no test liquid was applied from the thickness [μm] of the hemostatic films 1 to 6. The results are summarized below (Table 6). [Table 6]
[0062] Whole blood F and G were collected from two volunteers. Using whole blood F and G (n=3), the time (min) until the hemostatic film adhered to the glass plate was measured in the same manner as in Example 1. The results are summarized below (Table 7). The t-test was performed against the PET film. [Table 7] *p<0.05 **p<0.01 ns not significant
[0063] The relationship between the thickness of the layer containing cationic cellulose and the adhesion time shown in Example 2 is summarized in Figure 4. As shown in Figure 4, the adhesion time was shorter as the thickness of the topical hemostat increased. This indicates that the thickness of the layer containing cationic cellulose in the topical hemostat affects the hemostatic effect, specifically, the thicker the layer, the better the hemostatic effect of the topical hemostat.
[0064] Example 3 [Thickness of layer containing cationic cellulose] Hemostatic Films 7 to 9 were prepared using Test Solutions 7 to 9 in the same manner as in Example 2. The thicknesses [μm] of Hemostatic Films 7 to 9 were measured in the same manner as in Example 2. The results are summarized below (Table 8). [Table 8]
[0065] The time (minutes) until the hemostatic films 7 to 9 were adhered to the glass plate was measured in the same manner as in Example 2. The results are summarized below (Table 9). The t-test was a test against the PET film. [Table 9] *p<0.05 **p<0.01 ns not significant
[0066] As shown in Table 9, the topical hemostat having a layer thickness containing cationized cellulose of 6.7 μm exhibited hemostatic activity. [Explanation of symbols]
[0067] 1. Local hemostatic agent 2 Tourniquet Pads 21 First principal surface 22 Second principal surface 3 Backing material 31 First surface 32 Second surface 41 First release paper 42 Second release paper
Claims
1. A topical hemostatic material comprising a substrate having a first main surface and a layer containing cationic cellulose on the first main surface side, the layer containing cationic cellulose having a thickness of 16 μm or more, A topical hemostatic material, wherein the cationic cellulose has a molecular weight of 1,000,000 or more.
2. 2. The topical hemostat of claim 1, wherein the substrate is a structure of cotton, PET, and rayon, or a mixture thereof.
3. A method for producing a topical hemostat, comprising the steps of: applying a mixture comprising cationized cellulose in a solvent to at least one surface of a substrate; and removing the solvent from the mixture and forming a layer containing cationized cellulose on at least one surface of the substrate; Including, The mixture has a viscosity of 13 mPa·s or more, The cationic cellulose has a molecular weight of 1,000,000 or more; and The manufacturing method, wherein the layer containing the cationized cellulose has a thickness of 16 μm or more.
4. The method according to claim 3 , wherein the solvent is water, an alcohol, or a mixture thereof.
5. The method according to claim 3 or 4, wherein the substrate is a structure made of any one of cotton, PET, and rayon, or a mixture thereof.
6. 3. A topical hemostat according to claim 1 or 2, comprising a substrate and a layer comprising cationic cellulose on at least one side of the substrate. A mixed solution comprising cationic cellulose in a solvent, the mixed solution having a viscosity of 13 mPa·s or more, for producing the topical hemostat, The cationic cellulose has a molecular weight of 1,000,000 or more; and The mixture, wherein the layer containing the cationic cellulose has a thickness of 16 μm or more.
Citation Information
Patent Citations
Clay-based hemostatic agent and dispensing device thereof
JP2010520783A
Degradable hemostat composition
JP2016522208A
Hemostatic material and wound coating material
JP2017140231A
Hemostatic material and wound dressing material containing same
WO2019026177A1